Prevalence of leakage and its negative impact on quality of life in people living with a stoma in the UK. (8th September 2022) - Osborne, Wendy; White, Maddie; Aibibula, Miriayi; Boisen, Esben Bo; Ainsworth, Rachel; Vestergaard, Martin
Abstract : Background: People with a stoma are reported to experience leakage, which negatively impacts patient quality of life (QoL). Aim: To assess the impact of leakage experienced by individuals with a stoma in the UK. Methods: Data were analysed from 301 patients living in the UK who completed a questionnaire concerning the physical and psychosocial impact of living with a stoma. Findings: Most respondents had had their stoma for more than 5 years. Nine out of 10 worried about leakage to varying degrees and half the respondents accepted that this was a worry they had to live with. Almost 70% experienced leakage onto clothes within the preceding year, and 28% experienced this monthly. Peristomal skin complications were experienced by 82% of respondents, the severity of which correlated with reductions in QoL. Conclusion: Despite the consequential negative impact of leakage on QoL, individuals are not seeking advice to resolve leakage-related issues, including from their specialist stoma care nurse.